TRACING THE PHILOSOPHY OF RATIONALISM IN THE BOOK "MENGHILANG MENEMUKAN JATI DIRI" BY FAHRUDDIN FAIZ - Damanik, Agusman; Prayogo, Agung; Siregar, Muklis; Astaman, Raden Bagus; Syawal, Rakhmat; Indah, Fasrah (Tajdid, 2023)
This article aims to explore Fahruddin Faiz's work entitled disappearing, finding one's identity, which is phenomenal, especially in relation to its philosophical content. Next, this article will explore the deep thoughts that are the driving force for change and a deeper understanding of the nature of oneself. By providing a systematic introduction to the traces of the philosophy of rationalism. This paper is a type of Library Research research with a descriptive approach. The research process began with an intensive study of the contents of the book, where every word and concept presented by Faiz was analyzed to explore an understanding of rationalism. Next, secondary data collection was carried out through searching for related literature in scientific journals, publications and trusted web sources. Data analysis uses content analysis in the stages of data reduction, data presentation and drawing conclusions. The findings provide confirmation that can connect the reality of rationalist thinking with life that is very close to us. Fahruddin Faiz in his book wants to emphasize that the activities carried out in everyday life are related to the philosophy of rationalism brought by Descartes. The substance in this book states that finding one's true self has substance that encourages humans to have an awareness of the importance of correct philosophy. By philosophizing correctly the process of finding the meaning of life will be achieved